Estimation of the Fecundity of Jat Puti, Puntius sophore (Hamilton) (Journal of Environmental Science and Natural Resources, 2013)
The fecundity of 100 gravid female fishes of Jat puti, Puntius sophore, was collected from the experimental ponds of the Field Laboratory Complex, Faculty of Fisheries, Bangladesh Agricultural University (BAU), Mymensingh was estimated during the period from June to August 2011. Collected samples were clustered month-wise: group A (collected in June), group B (collected in July) and group C (collected in August). The estimated fecundity ranged of 7951 to 17670; 8135 to 23053 and 12461 to 15105 eggs and the mean gonadosomatic index (GSI) of 23.44 ± 2.50; 30.47 ± 4.52 and 28.43 ± 2.99 was estimated for the fish group of A, B, and C, respectively. The relationship between fecundity and total length was linear and it was expressed as: Ln F= 1634 ln TL-1972; Ln F= 119405 ln TL-273.53 and Ln F= 1831.6 ln TL+ 825.31 in group A, B, and C, respectively. The regression equation between body weight and total length was linear and it was expressed as: Ln W= 2.2128 ln TL- 0.7048; Ln W= 2.0207 ln TL+ 0.3493 and Ln W= 1.4438 ln TL+ 5.5694, in group A, B, and C, respectively. The regression equation between body weight and fecundity was linear and it was expressed as: F= 656.84 W+199.96, F= 438.16 W+2470, F= 1116.1 W-3433.5, in group A, B, and C, respectively. The fecundity was highly correlated with the total length, and body weight and P. sophore may be a medium fecund fish.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14833 J. Environ. Sci. & Natural Resources, 5(2): 295-300 2012